Berberine inhibits the tarO gene to impact MRSA cell wall synthesis - Gu, Xuemei; Zhou, Fangfang; Jiang, Mingming; Lin, Ming; Dai, Yue; Wang, Wei; Xiong, Zhongbo; Liu, Han; Xu, Minyi; Wang, Lei (Scientific reports, 2025)
Hospital and community-acquired infections caused by Methicillin-resistant Staphylococcus aureus (MRSA) have emerged as a significant public health challenge, highlighting the urgent need for novel antibiotics. In response, the antibacterial properties of natural products derived from traditional plants are being investigated as potential treatments for multidrug resistance. This study demonstrates the potent antibacterialimoact of Berberine (BBR), a compound derived from traditional Chinese medicine, against the community-associated MRSA (CA-MRSA) strain USA300 LAC. Through a comprehensive series of in vitro antibacterial experiments and gene-level investigations, we discovered that BBR compromises the integrity of the USA300 LAC cell wall structure. This mechanism of action is likely attributed to the inhibition of the tarO gene, which encodes a critical enzyme in the initial stage of wall teichoic acid (WTA) biosynthesis, thereby suppressing WTA synthesis, an essential component of the cell wall. Additionally, BBR upregulates the expression of lytic enzymes LytM and SsaA, resulting in accelerated hydrolysis of peptidoglycan, a major structural element of the cell wall. This disruption ultimately leads to the destruction of the USA300 LAC cell wall. Moreover, combined antibacterial assays reveal that BBR synergistically enhances the antibacterial effect of Oxacillin against USA300 LAC. Overall, our findings elucidate the antibacterial mechanism of BBR, a traditional Chinese medicine monomer, against MRSA and highlight its promising potential for clinical application in the treatment of MRSA.